AB0147 GENE EXPRESSION PROFILES OF PRIMARY SJÖGREN'S SYNDROME ASSOCIATED THROMBOCYTOPENIA IN B-LYMPHOCYTE USING HIGH-THROUGHPUT SEQUENCING. (2nd June 2020) - Zhang, S.; Qu, J.; Wang, L.; Li, M.; Zeng, X.
Abstract : Background: Primary Sjögren's syndrome(pSS) is a classical systemic autoimmune disease. Thrombocytopenia is one of the hematological manifestations of pSS with great challenges in clinic. Objectives: To identify the candidate genes and functionally enriched pathways in the immune genesis and progression of primary Sjögren's syndrome (pSS) associated thrombocytopenia. Methods: High-throughput sequencing was performed on 3 patients with pSS, 3 patients with pSS associated thrombocytopenia and 3 healthy individuals. The differentially expressed genes (DEGs) were identified, and function enrichment analyses were processed. The protein-protein interaction network (PPI) was constructed, followed by calculation of topological characteristics and sub-module analysis in order to obtain hub DEGs. The expression of some hub genes was verified by Real-Time PCR in 24 pSS patients. Results: A total of 19 DEGs were identified. The enriched functions and pathway of the DEGs include Toll-like receptor signaling pathway, Salmonella infection, Viral protein interaction with cytokine and cytokine receptor, NF-kappa B signaling pathway and Human cytomegalovirus infection. Seven hub genes (TNF, IL1B, CXCL8, CCL3, CCL4, CCL3L1, CCL4L1) were identified and pathway enrichment analysis revealed that these genes were mainly enriched in toll-like receptor pathway. The relative expression of the CXCL8 mRNA in B-lymphocytes in patients with pSS associated thrombocytopenia was higher than that in the pSS without thrombocytopenia group. No differences were observed in the IL-1β or TNFα expression between these two groups. Conclusion: PSS associated thrombocytopenia might be a subset characterized by a systemic inflammatory state. The identification of upregulated genes involved in thrombocytopenia of pSS provides insight in disease pathogenesis and opens avenues for the design of novel therapeutic strategies. References: [1] Fox RI: Sjögren's syndrome. Lancet, 2005; 366: 321–31. [2]Baldini C, Ferro F, Elefante E, Bombardieri S. Biomarkers for Sjögren's syndrome. Biomark Med. 2018;12(3):275-286. [3]Hua F, Li Y, Zhao X, et al. The expression profile of toll-like receptor signaling molecules in CD19(+) B cells from patients with primary immune thrombocytopenia. Immunol Lett. 2016, 176:28-35. Acknowledgments: The authors apologize to all colleagues whose work has not been separately cited or discussed here due to limitations in space or knowledge. Disclosure of Interests: SHUO ZHANG: None declared, Jingge Qu: None declared, Li Wang: None declared, Mengtao Li: None declared, Xiaofeng Zeng Consultant of: MSD Pharmaceuticals